A cable neck‐restraint to live‐capture coyotes - Michael T. Wegan; Dwayne R. Etter; Jerrold L. Belant; Dean E. Beyer Jr.; Nathan J. Svoboda; Tyler R. Petroelje (Wildlife Society Bulletin)
ABSTRACT We evaluated a cable neck‐restraint for live capture of coyotes (Canis latrans) in Michigan, USA, from 6 January to 22 March 2011. We documented capture efficiency, selectivity, and animal welfare using criteria developed by the Association of Fish and Wildlife Agencies Best Management Practices and the International Organization for Standardization. We constructed cable restraints with an 8.9‐cm‐diameter minimum loop stop and reverse bend washer locks drilled to 4.8 mm, to more readily relax on 2.4‐mm‐diameter steel cable. Cable restraints were set for 938 trap‐nights during January–March 2011. Capture efficiency was 71.4% (n = 20 coyotes) and selectivity 95.0%. We performed necropsies (n = 11) or external examinations (n = 9) to evaluate capture‐related injuries and released coyotes fitted with Global Positioning System collars (n = 5) to estimate home‐range size. Mean individual injury score of necropsied coyotes was 5.0 ± SD 8.9 and mean total injury score was 7.3 ± SD 9.8; we observed no mortality of coyotes due to capture. Home range sizes of 2 coyotes (8.9 km2 and 16.6 km2) were within the 95% confidence interval of mean home‐range size of resident coyotes captured in foothold traps (16.0 km2 ± SD 5.7, n = 11). Our findings indicate this cable restraint configuration exceeds all Best Management Practices criteria and is suitable for the capture of coyotes in both wildlife management and research arenas. © 2014 The Wildlife Society.